AKTIVITAS EKSTRAK KULIT BAWANG MERAH (Allium ascalonicum L.) TERHADAP PERTUMBUHAN BAKTERI Streptococcus mutans PENYEBAB KARIES GIGI - Musdalipah Musdalipah; Randa Wulaisfan (Jurnal Ilmiah Farmasi Farmasyifa, 2018)
Onion (Allium ascalonicum L.) is one of the most commonly used spices other than as a cooking spice as well as traditional medicine. The use of red onions is restricted to the meat alone, while the skin contains many chemical compounds that can be used as antibacterials such as flavonoids, saponins, tannins, glycosides and steroids or triterpenoids regarded as waste. This study aims to determine the inhibition power of onion skin extract (Allium ascalonicum L.) on the growth of Streptococcus mutans bacteria. The type of research used was experimental research consisting of three treatments, two controls: positive control and negative control with three repetitions. This research is done by cylinder cup method. Onion skin extract was obtained from maceration using 96% ethanol solvent. The test sample in this study was made with concentrations of 10%, 20% and 30%. The results showed that onion skin extracts with concentrations of 10%, 20% and 30% had mean inhibitions of 1.33 mm, 2.12 mm and 2.51 mm. The result of ANOVA test showed that F count (205,098 > F table (3,478) so that BNT further test showed that there is real effect difference of onion skin extract on the growth of Streptococcus mutans bacteria.